Construcción de escenarios para la cadena forestal en Arauca (2014)
Construction of scenarios for a forestry chain in Arauca Using a prospective exercise, the construction of a scenario for the forest production chain in the Department of Arauca which, as a territorial entity, has a great agroforestry potential, is pro